Association between overweight/obesity and eating habits while watching television among primary-school children in the city of Shiraz, Iran. Issue 3 (27th November 2017) - Ghobadi, Saeed; Totosy de Zepetnek, Julia O; Hemmatdar, Zeinab; Bellissimo, Nick; Barati, Reza; Ahmadnia, Hoda; Salehi-Marzijarani, Mohammad; Faghih, Shiva
Abstract: Objective: It has been reported that television (TV) viewing is associated with childhood obesity in Western countries. The present study aimed to investigate the relationship between obesity and eating habits while watching TV among primary-school children in the Middle East. Design: Cross-sectional. Setting: Children were recruited from primary schools of four educational districts in Shiraz, Iran. Anthropometric indices of mass (kg) and height (m) were measured, and BMI (percentile) was calculated. Demographic characteristics, TV viewing behaviours and physical activity data were collected from parents during face-to-face interviews and a 3d dietary record was completed. Subject: Children ( n 607) aged 6–10 years. Results: Mean (sd ) age of children was 8·16 (1·37) years, of whom 9·1 and 8·4 % were overweight and obese, respectively. Children who spent ≥2 h watching TV on weekdays (OR=1·99; 95 % CI 1·09, 3·60) and weekend days (OR=1·86; 95 % CI 1·01, 3·43) had higher odds of being obese, even after adjusting for physical activity. Children who ate breakfast while watching TV had higher odds of being overweight v . those who did not watch TV while eating breakfast (OR=2·70; 95 % CI 1·02, 7·60). There were no associations between TV viewing during other meals (lunch and dinner) and overweight/obesity. Conclusions: TV viewing for ≥2 h daily increases the risk of being obese in Iranian children aged 6–10 years, independent of physical activity. Further, breakfast consumption while watching TV may increase the risk of overweight/obesity, independent of total TV viewing time.